2019
DOI: 10.4491/eer.2018.390
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of organic and nitrogen removal from domestic wastewater in a down-flow hanging sponge bioreactor

Abstract: A down-flow hanging sponge (DHS) bioreactor was operated for the treatment of domestic wastewater. The Stover-Kincannon model was applied for kinetic evaluation of the reactor performance during the operational period. As a result, the coefficient of determination (R 2) for straight lines of effluent concentration from the experimental data and from the predictive data of BOD5; NH4 +-N; and TN were 0.9727; 0.9883; and 0.9934, respectively. The calculation of saturation value constant (Umax-g L-1 d-1) and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
(67 reference statements)
1
1
0
1
Order By: Relevance
“…Conducting batch tests with the actual wastewater could describe that system more accurately or verify the default parameters. Review of biokinetic parameters has shown variances and value ranges for these parameters [19]. The biokinetic coefficients obtained from this study are within these ranges.…”
Section: Determination Of Biokinetic Parameters From Experimental Datasupporting
confidence: 72%
“…Conducting batch tests with the actual wastewater could describe that system more accurately or verify the default parameters. Review of biokinetic parameters has shown variances and value ranges for these parameters [19]. The biokinetic coefficients obtained from this study are within these ranges.…”
Section: Determination Of Biokinetic Parameters From Experimental Datasupporting
confidence: 72%
“…The μ max and K B for COD removal of this study were relatively higher than other studies such as up-flow anoxic-aerobic sludge reactor [13], up-flow aerobic-anoxic sludge bed reactor [24], integrated anaerobic-aerobic reactor [25], up-flow aerobic anoxic sludge fixed film [7], moving bed biofilm reactors [5,[26][27][28], biofilm processes [10,29], modified septic tank system [29], anaerobic-anoxic-aerobic moving bed bioreactors [20], and integrated rotating biological contactor-activated sludge system [31]. However, the values of μ max, and K B in this study were lower than those of the down-flow hanging sponge bioreactor by Nga [32], probably which used lower strength wastewater in their studies. respectively.…”
Section: Determination Of Kinetic Coefficientsmentioning
confidence: 56%
“…Kai dumblo koncentracija yra optimali ir pastovi, lengviau valdyti nuotekų valymo procesą. Tarp nuotekų valymo parametrų nusistovėjus dinaminei pusiausvyrai, įmanomas procesų modeliavimas (Nga et al, 2020). Kad būtų galima lengviau ir giliau suprasti nuotekų valymo VD sistemos procesus, IWA užduočių grupė sukūrė keletą veikliojo dumblo modelių (Ayoub, 2018).…”
Section: įVadasunclassified